Can gold Dinar replace fiat money as currency? / Noraini Peie … [et al.] - Peie, Noraini; Mohamad, Saadiah; Mohamad Yusoff, Nur Syahirah; Joreme, Aidaty Aqilah; Rosli, Mohd Azizam (Universiti Teknologi Mara Selangor, 2017)
Currency instability often leads to economic crisis. This can be seen in period of worldwide economic recession in 1933, Mexican Peso crisis in 1995, currency depreciation in Southeast Asia in 1997 and 1998, and the Russian Ruble crisis in 1998. These crises have led to a discourse on fiat money as a possible culprit to the crises due to its inherent promotion of speculation, debt and interest related economy. The currency crises have also resurfaced the discourse on using gold as a currency. This paper discusses the advantages of using gold dinar that enables it to be a superior currency than the existing fiat money. The paper further examines the possibility of replacing fiat money with the gold dinar and recognises that the implementation of gold dinar proves to be problematic under current realities. One of the major problems related to fiat money is that of credit creation. The paper argues that if the Islamic banking industry under the control of central bank could limit credit creation to prevent excessive growth of money, then the use of fiat money could be defended. In addition, current developments in crypto and digital currency could make the discourse of going back to gold in the future rather obsolete.